2019
DOI: 10.1039/c9ra03653a
|View full text |Cite
|
Sign up to set email alerts
|

EG/TPU composites with enhanced flame retardancy and mechanical properties prepared by microlayer coextrusion technology

Abstract: In this work, expandable graphite (EG)/thermoplastic polyurethane (TPU) composites with excellent exfoliation, dispersion and two-dimensional plane orientation of the EG fillers were manufactured by microlayer coextrusion technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…The effect of the retardants is influenced by many factors. In the literature [17], the EG/PU composites prepared with their method showed a V-0 flame retardance level, whereas EG/PU composite prepared by conventional blending only showed a V-2 flame retardance level. Results in the literature [9] showed that the flame-retardant efficiency got better with the increase in the density of PU foam at the fixed EG weight percent, or with an increase in the EG weight percent at the fixed foam density.…”
Section: Introductionmentioning
confidence: 98%
“…The effect of the retardants is influenced by many factors. In the literature [17], the EG/PU composites prepared with their method showed a V-0 flame retardance level, whereas EG/PU composite prepared by conventional blending only showed a V-2 flame retardance level. Results in the literature [9] showed that the flame-retardant efficiency got better with the increase in the density of PU foam at the fixed EG weight percent, or with an increase in the EG weight percent at the fixed foam density.…”
Section: Introductionmentioning
confidence: 98%
“…Being an organic polymer, TPU is extremely flammable (when exposed to flame, produces volatile polymer fragments which are oxidized in the presence of atmospheric oxygen producing more heat. This forms cyclical combustion that continues to burn until the polymer decomposes) with an LOI value of 19%, and on incorporation of the FR additives, it improved significantly 39,40 . After incorporating 2% FR4 in TPU (labeled as FR4TPU 2 ), the LOI value reached up to 33.4%.…”
Section: Resultsmentioning
confidence: 99%
“…21 Thus, TPUs have been used in a wide range of application fields such as coatings and production in the foams, wires, cables, breathable films, sports, textiles, artificial tissue, and automotive. 2225 However, despite these versatile features, TPU possesses some drawbacks such as long degradation time in nature, low thermal stability, low mechanical strength, low durability, and poor aging properties. 26 Furthermore, the fundamental difficulty for TPUs is that TPU illustrates the low stress and low modulus when the strains reached the intermediate level and when the load is applied.…”
Section: Introductionmentioning
confidence: 99%